National Medical Expenditure Survey, 1987: Household Survey, Dental Visit Data (Public Use Tape 14.3) ([Verlag nicht ermittelbar], 1993)
The Household Survey is one of the three major components of the 1987 National Medical Expenditure Survey (NMES). (The other two components are the Survey of American Indians and Alaska Natives [SAIAN] and the Institutional Population Component.) Like its predecessors, the 1987 NMES provides information on health expenditures by or on behalf of families and individuals, the financing of these expenditures, and each person's use of services. The Household Survey was fielded over four rounds of personal and telephone interviews at four-month intervals. Baseline data on household composition, employment, and insurance characteristics were updated each quarter, and information on all uses of and expenditures for health care services and sources of payment was obtained. The data on Public Use Tape 14.3 provide information on dental visits for calendar year 1987. The data file contains one record per dental visit for each eligible person in the Household Survey who reported a dental visit during 1987, and who responded for his/her entire period of eligibility. In addition, each record contains basic person-level demographic information for the sample person, including age, sex, race, and ethnicity. Information is also supplied on type of service obtained during the dental visit, dates of service, and medical condition (ICD9-HIS codes) if the visit was due to accident or injury.